Peran Kepuasan Pengguna Memediasi Pengaruh Kualitas Layanan Terhadap Loyalitas Pengguna Aplikasi MyTelkomsel di Denpasar - Keysha Valerie Helwina Alowaes; I Wayan Santika (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Digital transformation has shifted Indonesian society toward the adoption of digital ecosystems, including the use of the MyTelkomsel application as a self-service platform for Telkomsel customers. Although application downloads continue to increase, the number of monthly active users remains relatively low and is accompanied by various complaints regarding digital service quality. This study examines the mediating role of user satisfaction in the relationship between service quality and user loyalty toward the MyTelkomsel application in Denpasar. A quantitative approach with a causal associative design was employed. Data were collected from 130 respondents selected using purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that service quality has a positive and significant effect on both user loyalty and user satisfaction. User satisfaction also positively and significantly affects user loyalty and partially complements the relationship between service quality and user loyalty. These findings highlight the importance of improving digital service quality through solution-oriented customer experiences and stronger emotional engagement to enhance user loyalty.